Implementation Gender-Responsive Budget: The Constraints and Their Coping Strategies - Anggraeni Nur Siswiraningtyas; Indrawati Yuhertiana (Department of Public Administration, Universitas Negeri Surabaya, 2021)
This study aims to evaluate the implementation of the gender-responsive budget, its constraints and the strategies to cope with it. This research is motivated by the lack of response of both central and local governments to implementing gender-responsive budget ideas. This study applied the systematic literature review (SLR) method through three stages: Planning, Conducting and Reporting on research results published over the past five years in five international scientific databases, namely the SAGE Journal, Science Direct, Springer Link, Emerald and Google Scholar. The results showed that the implementation of gender-responsive budgets requires strong support from the government and citizens. The obstacles faced in implementing a gender-responsive budget are weak supporting policies, lack of government commitment, lack of understanding of gender concepts, low political support, and reluctance to change. Then the strategies to overcome these obstacles are: determining the focus of budgeting, strengthening the dimension of communication, strengthening commitments, strengthening the quality of human resources, establishing planning and budgeting sections, and building cooperation with institutions. Since the study applied the systematic literature review (SLR) method, the study has a limitation regarding first-hand data. It suggested further research with first-hand data to find out more detail and contextual information on the implementation of the gender-responsive budgets in respective government institutions. Abstrak Studi ini bertujuan untuk mengevaluasi pelaksanaan anggaran responsif gender, kendalanya, dan strategi mengatasinya. Penelitian ini dilatarbelakangi oleh kurangnya respon pemerintah baik pusat maupun daerah dalam mengimplementasikan gagasan anggaran yang responsif gender. Penelitian ini menerapkan metode systematic literature review (SLR) melalui tiga tahap: Planning, Conducting dan Reporting terhadap hasil penelitian yang dipublikasikan selama lima tahun terakhir di lima database ilmiah internasional, yaitu SAGE Journal, Science Direct, Springer Link, Emerald dan Google Scholar. Hasil penelitian menunjukkan bahwa implementasi anggaran yang responsif gender membutuhkan dukungan yang kuat dari pemerintah dan masyarakat. Kendala yang dihadapi dalam mengimplementasikan anggaran yang responsif gender adalah lemahnya dukungan kebijakan, kurangnya komitmen pemerintah, kurangnya pemahaman konsep gender, rendahnya dukungan politik, dan keengganan untuk berubah. Kemudian strategi untuk mengatasi kendala tersebut adalah: penentuan fokus penganggaran, penguatan dimensi komunikasi, penguatan komitmen, penguatan kualitas sumber daya manusia, pembentukan seksi perencanaan dan penganggaran, serta membangun kerjasama dengan institusi. Karena penelitian ini menerapkan metode systematic literature review (SLR), penelitian ini memiliki keterbatasan mengenai data primer. Untuk mengetahui informasi lebih detail dan kontekstual tentang pelaksanaan anggaran responsif gender di masing-masing instansi pemerintah, disarankan penelitian empirik dengan menggunakan data primer. Kata kunci: anggaran responsif gender, pengarusutamaan gender, Systematic Literature Review (SLR)